2022
DOI: 10.1177/1069031x211073179
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Acceptance Across Cultures: The Roles of Collectivism, Empathy, and Homophily

Abstract: How does culture influence vaccination acceptance? This is an important question facing managers, policymakers, and global health organizations. Even with effective vaccines for highly contagious diseases, humankind remains at risk from vaccine hesitancy. We conduct a largescale multilevel analysis of more than 400,000 survey respondents, finding that COVID-19 vaccination intentions are higher among people from countries higher in cultural collectivism (Study 1). Follow-up studies indicate that vaccination acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…These nuanced dimensions of vertical and horizontal individualism–collectivism have important implications for how culture may influence COVID-19 prevention. For example, vertical hierarchism may produce greater obedience and horizontal egalitarianism greater empathy for others (Atalay & Solmazer, 2021 ; Leonhardt & Pezzuti, 2022 ) – leading to greater uptake of COVID-19 prevention behaviors, regardless of their individualism and collectivism. Indeed, while collectivism may be generally predictive of better uptake of prevention behaviors, egalitarian individualists might also be inclined to comply with public health guidance, even if it requires some self-sacrifice.…”
Section: Nuanced Models Of Cultural Orientationmentioning
confidence: 99%
“…These nuanced dimensions of vertical and horizontal individualism–collectivism have important implications for how culture may influence COVID-19 prevention. For example, vertical hierarchism may produce greater obedience and horizontal egalitarianism greater empathy for others (Atalay & Solmazer, 2021 ; Leonhardt & Pezzuti, 2022 ) – leading to greater uptake of COVID-19 prevention behaviors, regardless of their individualism and collectivism. Indeed, while collectivism may be generally predictive of better uptake of prevention behaviors, egalitarian individualists might also be inclined to comply with public health guidance, even if it requires some self-sacrifice.…”
Section: Nuanced Models Of Cultural Orientationmentioning
confidence: 99%
“…In this first of two special issues, Wood (2022) offers a persuasive commentary on the problems addressed in this special issue, followed by five articles examining key issues related to consumers’ behaviors during the COVID-19 pandemic and offering compelling direction for marketing managers based on their collective findings. In the first article in the special issue, Leonhardt and Pezzuti (2022) investigate the critical—and, at times, controversial—issue of vaccine acceptance across cultures and report that vaccination intentions are higher among people from countries higher in collectivism. Next, two articles examine consumers’ consumption behaviors during the pandemic.…”
Section: Well-being Topics and The Special Issue(s)mentioning
confidence: 99%
“…Emphasizing community benefits in health messaging has also been shown to increase vaccination in individualistic-leaning societies [ 11 ]. This phenomenon may function at both the community and individual levels; data comparing COVID-19 vaccine uptake across 50 countries found that vaccine intentions were higher in countries with more collectivistic cultures and that individuals from individualistic cultures who endorsed collectivistic values were more likely to accept a COVID-19 vaccine [ 12 ]. What is unknown, and what we investigate in this paper, is the extent to which the collectivistic or individualistic orientation in society can be made salient through vaccine videos and whether such heightened salience affects how people view and interpret the underlying message to get vaccinated.…”
Section: Introductionmentioning
confidence: 99%